РОЗУМІННЯ ПОНЯТТЯ «ОСОБИСТА СОЦІАЛЬНА ВІДПОВІДАЛЬНІСТЬ» МАЙБУТНІМИ СПЕЦІАЛІСТАМИ ФАРМАЦІЇ - Ткаченко, Н. О. (Фармацевтичний часопис, 2015)
UNDERSTANDING OF THE CONCEPT OF "PERSONAL SOCIAL RESPONSIBILITY" BY THE FUTURE SPECIALISTS IN PHARMACY Tkachenko N.O. Zaporizhzhia State Medical University, Zaporizhzhia, Ukraine Summary: In the article is theoretically soundly formation of social responsibility as a professional competence by the future specialists in pharmacy. The competence of the "social responsibility" is a factor converting the obtained professional knowledge and skills in system of views on social value of pharmacy, pharmaceutical organizations, herself and heir place in the pharmaceutical system. Analyzed of understanding "personal social responsibility" future specialists of pharmacy and their self-esteem themselves as the responsible person. Key words: social responsibility, pharmacy, personal responsibility, students Introduction. Social responsibility (SR) has a complex hierarchical structure, in which the main role belongs to the individual level, where a person is the subject of specific activities. The essence of personal social responsibility (PSR) subjects Pharmacy today is treated differently. This is the problem of defining it as a concept, its assessment methodology, forming system. Purpose of the work. The study of the essence of PSR within the pharmaceutical activity, and identify the level of completeness and understanding of this concept future specialists of pharmacy. Methods. We used: methods of analysis and synthesis, logical knowledge, comparison, generalization, content analysis and survey. We interviewed 167 graduating students of pharmaceutical faculty of Zaporizhzhya State Medical University correspondence course on a specialty "Pharmacy". Results and discussion. To clarify how students understand the definition of 'PSR' and completeness of the content, we proposed nine characteristics of PSR behavior specialist pharmacy with the ability to formulate other features to the discretion of the respondents. For ease of processing the results, respondents have conditionally divided into five groups. Group A determined performance characteristics elected students from 100% to 80%; Group B - from 79% to 60%; Group C - from 59% to 40%; Group D - from 39% to 20%, and Group E - below 20%. Analysis of the responses showed that in group A and group E was not included any of the characteristics of the PSR, that is, the majority of students today do not have a formed opinion on the existence of a single specialist pharmacy PSR. The group B owns only one response: 66.47% of respondents said "willingness to answer for their actions." Group C has the highest number of characteristics - 6 choices. Group D to identify options for the students' answers such as "socially responsible activities" and "self-esteem and self-reporting." Also, the survey respondents were asked to rate their personal responsibility for the individual parameters. This is very important: the responsibility to others begins with an assessment himself and his actions. Conclusions. The effectiveness of training and education of future pharmacists significantly increased in the case where the formation of the PSR recognizes the essential part of their training. Studies have shown that the vast majority of future specialists familiar with the concept of PSR, but rather the fullness of its definition varies. Undergraduate of correspondence course don’t have the shaped consensus as to the manifestations of SR by the pharmaceutical worker. Revealed significant divisions in the original concept definitions of the term PSR. Requires develop a model of social responsibility among university students of pharmaceutical profile and a common approach in teaching of the individual organizational and management disciplines.